Enhancing corn blight control: synergistic interaction between Bacillus subtilis SL-44 and hexaconazole via dual targeting of cell wall and membrane - Fan, Zhongdi; Wang, Wenfei; Chen, Ji; Nie, Haiteng; Jia, Wenjie; Min, Jiali; Wu, Zhansheng; Tian, Fei; Chang, Xiaojian; He, Yanhui (Frontiers in Microbiology, 2026)
Long-term reliance on chemical fungicides has given rise to issues such as pesticide residue and resistance. Combining fungicides with biological control agents, to reduces the dosage of chemical fungicide has become an important strategy. The synergistic mechanism of Bacillus subtilis SL-44 and chemical fungicide hexaconazole in controlling corn blight caused by Rhizoctonia solani, were investigated in present study. The results showed that both SL-44 and hexaconazole inhibited Rhizoctonia solani growth, and the SL-44 and hexaconazole compound at a 1:9 ratio exhibited significant synergy, with a toxicity ratio of 1.41. Optical and scanning electron microscopy revealed that the combined treatment induced the most severe mycelial damage in R. solani compared to individual Bacillus subtilis SL-44 or hexaconazole. In addition, the hexaconazole significantly reduced ergosterol content (by 101.63 μg/g), indicating strong inhibition of cell membrane. On the other hand, B. subtilis SL-44 caused greater cell wall damage, increasing chitinase and β-1,3 glucanase activities by 78.43 U/mL and 0.62 U/mL, respectively. The enhanced efficacy of the combination likely stems from the synergistic effect of these two distinct antimicrobial mechanisms: fungicide action on the cell membrane and biocontrol agent action on the cell wall. Pot experiments confirmed these findings, with the combination achieving an inhibition rate of 72.29%, significantly higher than that of SL-44 (32.58%) or hexaconazole (63.58%) alone. Overall, these results suggest that combining B. subtilis SL-44 with hexaconazole is a promising eco-friendly strategy for controlling corn sheath blight, reducing reliance on chemical fungicides while improving disease control efficacy.